An introduction to Flask - Grinberg, Miguel (O'Reilly Media, 2014)
"Get started with Flask, the popular web framework that's small, lightweight, and powerful. This video tutorial uses use short and simple examples to help beginning Python developers explore the features of Flask and some of its extensions. You'll learn topics central to most web applications - routing, templates, web forms, and user sessions - along with a brief introduction to databases and user logins."--Resource description page.